Photoessay: Melanesian mythical places with unreported conflicts: A portrait - Ben Bohane (Asia Pacific Network, 2014)
As a photojournalist who has lived and journeyed through the ‘Black Islands’, Vanuatu resident Ben Bohane was drawn to them because they still seemed like mythical and remote places in an increasingly familiar world, while many of their conflicts went largely unreported. There were family connections too. So beginning in 1994, he ran a naval blockade to cover the war in Bougainville and soon found others too, wars the rest of the world had conveniently forgotten: in East Timor, West Papua as well as Bougainville. Then there were riots in New Caledonia, civil war in the Solomon Islands and coups in Fiji. The following is an introductory extract and a portfolio of images from Bohane's 2013 monograph, Black Islands: Spirit and War in Melanesia. Caption: Radio Free Bougainville on the air with ‘Philip’ at the microphone. Central Bougainville, PNG 1994 (p. 157). © BEN BOHANE